2021
DOI: 10.1515/reveh-2021-0111
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to toxic occupations and their association with Parkinson’s disease: a systematic review with meta-analysis

Abstract: Objectives Earlier longitudinal reviews on environmental and occupational toxins and Parkinson’s disease (PD) risk have limitations. This study aimed to determine the strength of association between three types of toxic occupational exposures and the occurrence of PD by diagnostic methods. Methods A search was conducted of EMBASE, PubMed/Medline, Toxnet, LILACS, and Cochrane Library databases for longitudinal studies that ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…In an in vitro experiment, siRNA to IL-37 (siIL-37) was transfected into human PBMCs stimulated by LPS. After IL-37 expression was specifically silenced, the production of IL-6 and other cytokines increased in a dose-dependent manner [82], indicating IL-37 can inhibit the inflammatory effect of IL-6 and play an anti-inflammatory role. Irene Tsilioni et al found that neuropeptide NT can stimulate human microglia to secrete IL-1β, CXCL8, and other cytokines that can be inhibited by IL-37 [91]; however, the specific mechanism underlying this inhibition remains unclear.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In an in vitro experiment, siRNA to IL-37 (siIL-37) was transfected into human PBMCs stimulated by LPS. After IL-37 expression was specifically silenced, the production of IL-6 and other cytokines increased in a dose-dependent manner [82], indicating IL-37 can inhibit the inflammatory effect of IL-6 and play an anti-inflammatory role. Irene Tsilioni et al found that neuropeptide NT can stimulate human microglia to secrete IL-1β, CXCL8, and other cytokines that can be inhibited by IL-37 [91]; however, the specific mechanism underlying this inhibition remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Exploring the roles of IL-37 in AD can be a promising direction for future research because caspase-1 is also an enzyme that cleaves the precursor of IL-37 and renders it active [31]. In addition, IL-37 has been shown to inhibit the inflammatory effects of other inflammatory cytokines, such as IL-6 and IL-1β in many other diseases [77][78][79][80][81][82]. In a temporomandibular joint study, IL-37 could convert M1 type macrophages to M2 type, thus alleviating inflammation [83].…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, given the differentially methylated promoter of the TNF- α gene in PD [ 23 ], the role of cigarette smoking in this relationship should be further explored. Additionally, smoking seems to affect histone acetylation and de-acetylation, and affect the expression of miRNAs in non-nerve tissues [ 82 , 83 , 84 , 85 ]. Thus, DNA methylation and possibly other epigenetic modifications might mediate the effects of smoking in PD.…”
Section: Environmental Impact On Epigenetic Modifications In Pdmentioning
confidence: 99%
“…However, environment clearly also makes an important contribution to PD. Epidemiological studies have shown that exposure to pesticides increases the risk of PD (Chambers-Richards et al, 2021; Fernagut et al, 2007; Hatcher et al, 2008). In particular, both the fungicide maneb (MN, manganese ethylene-bis-dithiocarbamate) and the herbicide paraquat (PQ) have been associated with PD (Ascherio et al, 2006; Wang et al, 2011).…”
Section: Introductionmentioning
confidence: 99%